Irish community-based social enterprises : an investigation into their rationale, activities and motivations - Germaine, Kenneth (Trinity College (Dublin, Ireland). Department of Geography, 2010)
The subject of this thesis was community-based social enterprises in Ireland, especially relating to two questions - why were social enterprises established and why did social enterprises continue to exist? The outcomes of the research indicated that social enterprises were established to meet social objectives, primarily the needs of vulnerable groups in society and that the enterprise model was adopted for pragmatic reasons. The research also indicated that as social enterprises became more established the role of economic considerations became more important, predominantly as a result of the increased commitments to staff, customers, suppliers and funding agencies. The research also indicated that the activities of social enterprises were influenced by their location in either an urban or rural location, with the majority of self-sufficient social enterprises being located in urban areas and the majority of demand-deficient social enterprises being located in rural areas.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin